2020
DOI: 10.2337/dc19-1013
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Disability in KATP Channel Neonatal Diabetes

Abstract: OBJECTIVE Neonatal diabetes has been shown to be associated with high neuropsychiatric morbidity in a genotype-phenotype–dependent manner. However, the specific impact of different mutations on intellectual functioning is still insufficiently characterized. Specifically, only a small number of subjects with developmental delay have been comprehensively assessed, creating a knowledge gap about patients carrying the heaviest burden. RESEARCH DES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…Genetic diagnosis of potassium-channel neonatal diabetes is extremely important because affected neonates can be treated with sulfonylurea tablets [34]. In KCNJ11 PNDM, the genetic mutations are correlated with the severity of the neurological abnormalities, which were thought to improve with sulfonylureas, although recent data casts doubts on this concept [35]. Mutations in key pancreas development transcription genes (e.g.…”
Section: Heterogeneity Of Diabetes Within Types and Clinical Consequementioning
confidence: 99%
“…Genetic diagnosis of potassium-channel neonatal diabetes is extremely important because affected neonates can be treated with sulfonylurea tablets [34]. In KCNJ11 PNDM, the genetic mutations are correlated with the severity of the neurological abnormalities, which were thought to improve with sulfonylureas, although recent data casts doubts on this concept [35]. Mutations in key pancreas development transcription genes (e.g.…”
Section: Heterogeneity Of Diabetes Within Types and Clinical Consequementioning
confidence: 99%
“…1) . Early SU therapy may improve speech, motor, and cognitive disabilities, and re cent studies have identified a higher prevalence of neurodevelop mental disorders in particular geno types, although the correla tion of the genotypes with neurodeve lopmental impairment along with underlying pathophysiology re mains to be charac terized 22,23) . Although variations of genes enco ding the KATP channel are known to be the most common and second most common causes of PNDM and TNDM, respectively, genetic confirmation requires a considerable amount of time; how ever, recent literature suggests considering early SU therapy before a genetic diagnosis is made, to avoid the potential adverse effects of delayed therapy 1,24) .…”
Section: Discussionmentioning
confidence: 99%
“…Several variants with gain-of-function properties have been associated with ID: V59M, Y330C, V59A, G53D, R201C, C166Y, V59G, and Q52R. Most cases carry the V59M variant Supplementary Table 1, which shows clear association with ID symptoms (Svalastoga et al, 2020). Notably, Lin et al (2013) reported a case with gain-offunction derived from the S225T mutation and P226_P232del, suggesting that both gain-and loss-of-function mutations could lead to I-DEND.…”
Section: Kcnj6 (Girk2)mentioning
confidence: 99%
“…Sulfonylureas act as inhibitors of KATP channels and represent an optimum treatment for diabetes and they can ameliorate the related neurological disorders (Pearson et al, 2006). However, other studies have not detected any benefits of sulfonylureas on neurological symptoms (Sagen et al, 2004;Klupa et al, 2005;Svalastoga et al, 2020), suggesting that sulfonylureas can partially cross the blood-brain barrier, and that the improved neurological symptoms observed resulted from increased cerebellar perfusion (Fendler et al, 2013). Thus, ID could be initiated from gain-of-function or as a complication of neonatal diabetes or due to unknown mechanisms associated with KATP channel, which the partial effects of sulfonylureas on neurological symptoms cannot confirm.…”
Section: Kcnj6 (Girk2)mentioning
confidence: 99%